PHYTOCHEMICAL AND MEDICINAL STUDY OF LANTANA CAMARA LINN. (VERBENACEAE) - A REVIEW - BATTASE, LALITA; ATTARDE, DAKSHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Lantana camara is a plant from the family - Verbenaceae. It is found in many states of India, mostly in Jammu-Kashmir, Himachal Pradesh, Tamil Nadu, South India, Uttar Pradesh, and several parts of Maharashtra and other countries also. Mainly in disturbed areas, including roadside, railway tracks, and canals. It is an ornamental plant but, in ancient times, it was used traditionally. The plant having various traditional uses. Parts of plant extracts are used traditionally such as the healing of wounds, cuts, skin itches, and eczema. The plant containing many more phytoconstituents such as alkaloids, glycosides, saponins, steroids, terpenoids, carbohydrates, flavonoids, and coumarins. It has various pharmacological activities antioxidant, antimicrobial, antibacterial, antifungal, antiulcerogenic, anthelmintic, anti-hyperglycemic, anti-inflammatory, analgesic, anticancer, antitubercular, etc. It also having mosquito larvicidal activity. This review article was written by the study of many research and review articles from 1956 to March 2021 in which 72 articles were cited. This article reviewed different phytochemicals present in L. camara. The review draws attention to the traditional uses, analytical work, pharmacological activities, and toxicology of this plant and also the potential uses of this plant.